Пошаговое объяснение:
1) - 15-4х= - 8х+45
-4х+8х=45+15
4х=60
Х=60:4
Х=15
2) - 8х-17=3х-105
-8х-3х= - 105+17
-11х= - 88
Х=8
3) 2(у+3)=21-3у
2у+6=21-3у
2у+3у=21-6
5у=15
У=3
4) (2-с)+3(с-3)= - 13
2-с+3с-9= - 13
2с= - 13-2+9
2с= - 6
с= - 3
5) - 3(1-3b)-12=12
-3+9b-12=12
9b=12+3+12
9b=27
b=3
a) sin(t)*2cos(t)+1)=0
1) sin(t)=0
t=pi*n
2) 2*cos(t)+1=0
2*cos(t)=-1
cos(t)=-1/2
t=±arccos(-1/2)+2*pi/n
t=±(4*pi/3)+2*pi*n
б) (sin(t)-1)*(cos(t)+1)=0
1) sin(t)-1=0
sin(t)=1
t=(pi/2)+2*pi*n
2) cos(t)+1=0
cos(t)=-1
t=pi+2*pi*n
в) cos(t)*(2sin(t)+1)=0
1) cos(t)=0
t=(pi/2)+pi*n
2) 2*sin(t)+1=0
2*sin(t)=-1
sin(t)=-1/2
t=(-1)^n*arcsin(-1/2)+pi*n
t=(7*pi/6) +pi*n
г) 2sin(t)-sqrt(2))*(2*cos(t)+1)=0
1) 2*sin(t)-sqrt(2)=0
2*sin(t)=sqrt(2)
sin(t)=sqrt(2)/2
t=(pi/4)+pi*n
2) 2*cos(t)+1=0
2*cos(t)=-1
cos(t)=-1/2
t= ±arccos(-1/2)+2*pi*n
t=±(4*pi/3)+2*pi*n
a) sin(t)*2cos(t)+1)=0
1) sin(t)=0
t=pi*n
2) 2*cos(t)+1=0
2*cos(t)=-1
cos(t)=-1/2
t=±arccos(-1/2)+2*pi/n
t=±(4*pi/3)+2*pi*n
б) (sin(t)-1)*(cos(t)+1)=0
1) sin(t)-1=0
sin(t)=1
t=(pi/2)+2*pi*n
2) cos(t)+1=0
cos(t)=-1
t=pi+2*pi*n
в) cos(t)*(2sin(t)+1)=0
1) cos(t)=0
t=(pi/2)+pi*n
2) 2*sin(t)+1=0
2*sin(t)=-1
sin(t)=-1/2
t=(-1)^n*arcsin(-1/2)+pi*n
t=(7*pi/6) +pi*n
г) 2sin(t)-sqrt(2))*(2*cos(t)+1)=0
1) 2*sin(t)-sqrt(2)=0
2*sin(t)=sqrt(2)
sin(t)=sqrt(2)/2
t=(pi/4)+pi*n
2) 2*cos(t)+1=0
2*cos(t)=-1
cos(t)=-1/2
t= ±arccos(-1/2)+2*pi*n
t=±(4*pi/3)+2*pi*n
я не знаю сорян для меня слишком трудно